Betalains, the nature-inspired pigments, in health and diseases. Issue 18 (11th October 2019) - Rahimi, Parisa; Abedimanesh, Saeed; Mesbah-Namin, Seyed Alireza; Ostadrahimi, Alireza
Abstract: Betalains are unique nitrogen-containing pigments found exclusively in families of the Caryophyllales order and some higher order fungi, where they replace anthocyanin pigments. Betalains, consisting of betacyanins and betaxanthins are generally used as color additives in food. This review discusses on the favorable effects of acute and chronic consumption of betalains, whose edible sources consist primarily of red beetroots ( Beta vulgaris ) and prickly pears (fruit of the Opuntia genus of cacti). Moreover, it encompasses in vivo and in vitro studies about the bioavailability and bioaccessibility of betanin and indicaxanthin. It seems that treatment with betalains and betalain-rich diets is not only nontoxic but could also prove to be a promising alternative to supplement therapies in oxidative stress-, inflammation-, and dyslipidemia-related diseases such as stenosis of the arteries, atherosclerosis, hypertension, and cancer, among others. Due to its toxicological safety, accessibility, low price, biodegradability, and potentially advantageous biological effects on health, the incorporation of betalains in food manufacturing and related industries could pave the way to overcome current concerns over the health risks of artificial colors. Nevertheless, further studies using pure betalains are required to gain a deeper understanding of their precise biological functions.